2000
DOI: 10.1002/1521-3765(20000915)6:18<3377::aid-chem3377>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and1H-,13C- and15N-NMR Spectra of Ethynyl Isocyanide, H−C≡C−N≡C, D−C≡C−N≡C and Prop-1-ynyl Isocyanide, H3C−C≡C−N≡C, D3C−C≡C−N≡C: High Resolution Infrared Spectrum of Prop-1-ynyl Isocyanide

Abstract: Ethynyl isocyanide, H-C triple bond C-N triple bond C (1a), deuteroethynyl isocyanide, D-C triple bond C-N triple bond C (1b), prop-1-ynyl isocyanide, H3C-C triple bond C-N triple bond C (1c), and trideuteroprop-1-ynyl isocyanide, D3C-C triple bond C-N triple bond C (1d) are synthesized by flash vacuum pyrolysis of suitable organometallic precursor molecules (CO)5Cr(CN-CCl triple bond CClH) (5a), (CO)5Cr(CN-CCI=CClD) (5b), (CO)5Cr(CN-CCl=CCl-CH3) (5c) and (CO)5Cr(CN-CCI=CCl-CD3) (5d), respectively. Compounds 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(41 reference statements)
0
9
0
1
Order By: Relevance
“…In male rodents, aging and, to a lesser extent, deficits in memory performance, have been associated with changes in hippocampal gene expression (Blalock et al, 2003;Verbitsky et al, 2004;Rowe et al, 2007;Burger et al, 2008). These differences consist mostly of gene upregulation in middleaged male mice (15-month old) as compared with 2-monthold counterparts (Verbitsky et al, 2004).…”
Section: Gene-expression Changes In the Hippocampus During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…In male rodents, aging and, to a lesser extent, deficits in memory performance, have been associated with changes in hippocampal gene expression (Blalock et al, 2003;Verbitsky et al, 2004;Rowe et al, 2007;Burger et al, 2008). These differences consist mostly of gene upregulation in middleaged male mice (15-month old) as compared with 2-monthold counterparts (Verbitsky et al, 2004).…”
Section: Gene-expression Changes In the Hippocampus During Agingmentioning
confidence: 99%
“…There is clear evidence that a constellation of gene expression changes underlie hippocampal phenotype aging. Thus, gene expression studies in aging rodents have documented significant changes in hippocampal genes related to cholesterol synthesis, inflammation, transcription factors, neurogenesis, and synaptic plasticity (Blalock et al, 2003;Verbitsky et al, 2004;Burger et al, 2007Burger et al, , 2008Rowe et al, 2007). While those studies revealed that aging itself is associated with the majority of gene expression changes, a smaller portion of the transcriptional differences in the hippocampus are related to changes in learning and spatial memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…[8] HÀCCÀNC has been subsequently studied by HeI and HeII photoelectron spectroscopy, [9] millimeter-wave spectroscopy, [10] high-resolution FTIR spectroscopy, [11] and NMR spectroscopy. [12] Recently the very unstable CNÀCCÀCN molecule which had only been obtained before in an argon matrix and characterized by IR spectroscopy [13] was synthesized, and a broad study has been performed by a collaborative effort. [14] Propynyl isocyanide is the only other alkynyl isocyanide which has been obtained thus far in preparative quantities and studied by various spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Propynyl isocyanide is the only other alkynyl isocyanide which has been obtained thus far in preparative quantities and studied by various spectroscopic methods. [12,15] Recently, Thaddeus et al succeeded in generating HÀ(CC) n ÀNC (n 2,3) (approximately 0.1 to 1 picomole) along with large amounts of other compounds by electrical discharge in a molecular beam of butadiyne, propynenitrile, or others seeded in Ne. [16,17] The detection of the isocyanopolyyne molecules was based solely on Fourier transform microwave spectroscopy in combination with ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In den letzten Jahren gelang die Synthese einer Reihe kleiner Isocyanide wie z.B. CN-CN, [12Ϫ14] CN-NC, [15], H-CC-NC, [16,17] H 3 C-CC-NC, [17] und NC-CC-NC. [18,19] Von den drei isomeren Methanderivaten Malonodinitril, CH 2 (CN) 2 , Isocyanacetonitril, CH 2 (CN)(NC), und Diisocyanmethan, CH 2 (NC) 2 ist nur Malonodinitril [20] seit langem bekannt, gut charakterisiert und bei Raumtemperatur stabil.…”
unclassified